The Role of Product Quality and Price in Shaping Consumer Purchasing Decisions at Harvest Chicken Express Glenmore - Sholehuddin, Muhammad; Setiadevi, Shinta (Politeknik Negeri Jember, 2024)
Competition is getting tougher in the culinary field, making Harvest Chicken Express Glenmore need to understand the factors that influence consumer purchasing decisions when buying products. This study aims to examine and analyze the effects of the independent variables, partially and simultaneously, and determine which has the most dominant effect on the dependent variable. The research method uses a quantitative approach with a survey method with a sample of 40 people. Sampling technique with non-probability sampling technique and incidental sampling approach Multiple linear regression analysis techniques, multiple determination coefficients, F and t-tests, validity test, reliability test, and classic assumption test (normality test, multicollinearity, and heteroscedasticity) Tests were carried out with the IBM SPSS Statistics 25 software analysis tool. Multiple linear regression equation Y = 5.546 + 0.604X1 - 0.148X2 + 0.574X3 + e. Based on the results of the F test, the independent variables simultaneously have a significant effect on the dependent variable. The adjusted R2 test obtained a value of 74.2%. Based on the t-test, it was found that product quality (X1) and price (X3) had a significant effect, while service quality (X2) had no significant effect on consumer purchasing decisions. The most dominant independent variable influencing consumer purchasing decisions at Harvest Chicken Express Glenmore is product quality.